Karamentang Sungai Tutung: Application of ethnomathematics in learning mathematics reflection transformation material - Rahmadhani, Aulia Sefti; Yulia, Putri; Gunawan, Rilla Gina (CAHAYA PENDIDIKAN, 2024)
Learning mathematics related to culture is an effective alternative to mathematics. The Karamentang Sungai Tutung is a cultural object that is used as a marker for a kenduri sko event or thanksgiving for all the village residents for their harvest which is held every five years. In Karamentang there are geometric mathematical concepts that can be reflected on, namely parallelograms and rectangles. The aim of this research is to apply karamentang ethnomathematics in transformational reflection mathematics learning and see students' understanding of mathematical concepts. The research method used is a mixed method using the Kolmogorov-Smirnov Normality Test data analysis technique, hypothesis test (t-test), analysis of questionnaire results and interviews. This research data was obtained from observations, tests, questionnaires and interviews. The results of the research show that the effective t-test is t count < t table, namely 0.034517 < 2.109816 and the questionnaire results are more than the KKM of 79.51%. So it can be concluded that the application of ethnomathematics using the Tutung River Karamentang in mathematics learning reflective material in class.